Euphemism in Tshivenda : a socio-pragmatic analysis - Mudau, Mmbulaheni Lawrence (University of Limpopo, 2016)
This study examined Tshivenḓa euphemisms from a socio-pragmatic perspective within a framework of Politeness and Indirectness Communicative theories. According to Brown and Levinson (1987), Politeness Theory describes politeness as showing concern for people’s ‘face’ needs where ‘face’ means one’s public self-image. In terms of the Indirectness Communicative Theory, euphemism is a face saving mechanism which emphasizes mutual cooperation in a conversation. Euphemisms are described as substitutions of agreeable or inoffensive expressions for ones that may offend or suggest something unpleasant. They are words with meanings or sounds that are thought, somehow, to be nicer, cleaner or more elevated and they are used as substitutes for words deemed unpleasant, crude or ugly in sound or sense. The study adopted a descriptive and exploratory design within a qualitative research approach, based on the view that qualitative research aims at explaining complex phenomena by means of verbal description rather than testing hypotheses with numerical values. Furthermore, primary data were elicited from 25 participants of different ages, genders, educational levels, social status and occupations who are native speakers of the Tshivenḓa language by means of semi-structured interviews. Since this study involved working with humans, all ethical aspects were ensured. The study, which investigated the use of Tshivenḓa euphemisms, was conducted in seven social domains in Venḓa in the Vhembe District: local courts, churches, homes, hospitals, girls in seclusion, schools and electronic media. The study’s findings show evidence of the use of Tshivenḓa euphemisms in these various domains. However, the court domain seems not to use many euphemisms due to the fact that clear communication is required there; for two parties in a case to understand what is being said during the proceedings the use of roundabout indirect language is avoided – the courts believe in calling ‘a spade, a spade.’ Through the careful analysis of euphemisms, the study’s findings revealed that euphemisms have both positive and negative effects on language, including Tshivenḓa. Some of the positive effects of euphemisms revealed by this study include the ability to avoid directly naming what is deemed unpleasant; they make the language sound more v literary; and they allow people to discuss touchy or taboo subjects with ease. However, the findings also suggested that euphemisms may be disrespectful; they could hinder clear communication; they are deceptive; and they may lead to miscommunication and general confusion. Based on the findings of the study, it is recommended that the use of euphemisms in Tshivenḓa language should be reinforced in all social domains in order to enhance politeness; preserve the public self-image of the participants in communicative exchanges; and facilitate harmonious interpersonal relationships. It is also recommended that further study be undertaken to identify other factors that may affect the use of euphemisms in Tshivenḓa from other perspectives. Key concepts: Politeness; Euphemisms; Treadmill; Taboo; Face work
Thesis (Ph. D. (Tshivenda)) --University of Limpopo, 2016
Keywords: Politeness; Euphemisms; Treadmill; Taboo; Face work; Venda language - Euphemism; Euphemism